ШЫҢҒЫС АЙТМАТОВ ҲӘМ ҚАРАҚАЛПАҚ ӘДЕБИЯТЫ - Бекбергенова, М.Д. (FAN va JAMIYAT, 2018)
This article examines the study of the work of the famous Kyrgyz writer Chingiz Aitmatov. The artistic features of Chingiz Aitmatov’s prose are being studied. The ideological content of his novels and novels "Jamila", "Mother’s Field", "Goodbye Gulsary", "The White Parade", "And more than a century lasts a day," "When the mountains fall," etc. Also, questions of literary traditions of Ch. Aitmatov in the work of Karakalpak writers.